EFEKTIFITAS BASYARNAS DAN PENGADILAN AGAMA SEBAGAI LEMBAGA PENYELESAIAN SENGKETA ASURANSI SYARIAH DI INDONESIA - Winda Fitri (Fakultas Hukum, Universitas Internasional Batam, 2019)
The purpose of this study is to describe clearly and carefully about the process of dispute resolution on Sharia insurance in Indonesia referring towards law regulations and to acknowledge the law-effectiveness of BA-SYAR-NAS and the Religious Court as the institutions with equal authorities for Sharia insurance dispute settlement in Indonesia. The research method applied on this study is sociological legal approach. The data utilized are secondary and primary data. After the entire data have been collected, they were being processed and analyzed. The qualitative method were used to analyzed aspects as they were studied. Furthermore, the conclusion was drawn according to this study, alongside a descriptive elaboration. Based on the result of this research-study, it has been accounted that the process of dispute resolution of insurance could be settled by two legal institutions. According to the theory of the “Effectiveness of Law” by Soerjono Soekanto, BA-SYAR-NAS is more effective in terms of settling the dispute of Sharia insurance corresponding to the court principles of simple, efficient and low-cost. Nevertheless in reality, that the legal culture of the society leans more towards the Religious Court.